Pemanfaatan Media Sosial Komunitas Online Buibu Baca Buku Books Club dalam Memberdayakan Literasi Wanita - Anjani, Afifah; Samosir, Fransiska Timoria; Ginting, Richard Togaranta (BACA: Jurnal Dokumentasi dan Informasi, 2024)
The Bbbbookclub community consists of working mothers and homemakers, which aims to empower women so they have literacy and good knowledge. This community activity is carried out by utilizing socialmedia, active discussions and discussions about reading materials that are of interest to improve literacy.  This study aims to analyze the form of empowerment carried out by the Bbbbookclub community through digital platforms to improve literacy skills. This research uses a qualitative approach. Observation, interviews, and documentation carry out data collection. The data analysis technique uses a descriptive analysis method to describe an overview based on the data results. The results of the study show that the Bbbbookclub community can empower women's literacy, especially homemakers who are busy taking care of the household.  This can be seen from the participation of community members in various literacy activities and mothers' reading interest level after joining the Bbbbookclub community. The community's forms of empowerment are Reading Challenges, Book talks, and Digital content, including book recommendations. Through the conclusion of this study, it is known that the empowerment carried out by the Bbbbookclub community through social media can increase women's literacy, especially homemakers, through reading materials recommended by the community and community members.